“INCIDENCIA DEL CAPITAL HUMANO EN EL EMPRENDIMIENTO REGIONAL PARA 218 CANTONES DE ECUADOR: UN ENFOQUE USANDO MÉTODOS ESPACIALES, AÑO 2010 - Jimenez Soto, Cecibel Jackeline (2019)
Entrepreneurship is one of the most effective ways of dynamising the economy and promoting the economic development of a country. That is why the present work has as a general objective: to determine the relation of human capital at the regional level for 218 corners of Ecuador during the year 2010, through an econometric study using a method of space methods, in order to establish its impact on entrepreneurship. The data used were obtained from the National Institute of Statistics and Census (2010) and the Integrated System of Social Indicators of Ecuador (2010). The main results obtained from the method of least ordinary squares emphasize that human capital has a positive and statistically significant effect on regional entrepreneurship. With spatial space spatial (SAR), spatial error (SEM), and Durbin space (SDM) spatial dependence between variables was confirmed, with the exception of the SARMA model. To ensure the robustness and consistency of the parameters obtained, a set of control variables was incorporated: number of companies that export, income per capita, urban population, amount of training and training and index of regional competitiveness related to the allocations of the regions An implication of economic policy derived from the investigation is oriented to promote the birth of new companies, and to improve the access and the quality of the education.